2020
DOI: 10.1177/2325967120964471
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes, Return-to-Sport Status, and Reinjury Rates After Anterior Cruciate Ligament Reconstruction in Adolescent Athletes: Minimum 2-Year Follow-up

Abstract: Background: Significant variation exists in the published rates of return to sport after anterior cruciate ligament (ACL) reconstruction (ACLR). Functional outcomes and psychological response to injury have been implicated as factors that influence return to sport. Most studies focus on patients aged in the mid-20s, and less is known about this topic in adolescents. Purpose: To report midterm ACLR results for adolescent patients with regard to return to primary sport, patient-reported outcomes, and reinjury ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…There was, however, a difference in the patient-reported outcome (International Knee Documentation Committee Subjective Knee Evaluation Form score: 95.52 vs 82.76, p = 0.03) [34]. Fones et al [33] also found that patient-reported outcomes were significantly lower in the people who did not return to sport in adolescents after 2 years post-surgery. The results suggest that PROs may be able to detect ongoing symptoms affecting patients' wellbeing that cannot be fully detected using traditional functional test batteries [34].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There was, however, a difference in the patient-reported outcome (International Knee Documentation Committee Subjective Knee Evaluation Form score: 95.52 vs 82.76, p = 0.03) [34]. Fones et al [33] also found that patient-reported outcomes were significantly lower in the people who did not return to sport in adolescents after 2 years post-surgery. The results suggest that PROs may be able to detect ongoing symptoms affecting patients' wellbeing that cannot be fully detected using traditional functional test batteries [34].…”
Section: Discussionmentioning
confidence: 95%
“…The relationship between stability and the perception of stability becomes more prominent when preparing for return to play following an injury. Psychological readiness and physical performance have not been researched in people with CAI previously, however, it has been reported following ACL reconstruction (ACLR) surgery [33,34]. Following ACLR, it has been reported that there were no functional differences for any of the tests conducted between the participants who did and did not return to sport.…”
Section: Discussionmentioning
confidence: 99%
“…For the question "How would you rate your knee function on a 10-point scale?" the patients who underwent bilateral ACLR scored significantly lower compared with the unilateral ACLR group (median [IQR], 7 [5][6][7][8] vs 8 [7][8][9], respectively; P < .001). Within the bilateral ACLR group, there were no significant differences regarding knee satisfaction between the first and contralateral ACL-reconstructed knee (Table 3).…”
Section: Subjective Knee Functionmentioning
confidence: 99%
“…After the first ACLR, the bilateral ACLR group reported a higher return to the same sport (88% vs 54%; P < .001) and preinjury activity level (66% vs 45%; P ¼ .003) compared with the unilateral ACLR group. Patients in the bilateral ACLR group had a significantly higher Tegner score after the first ACLR (median [IQR], 8 [7][8][9] vs 6 [6][7][8] for the unilateral group; P < .001). After the second ACLR (in the bilateral ACLR group), 61% of the patients returned to the same sport and 41% returned to their preinjury activity level.…”
Section: Activity Levelmentioning
confidence: 99%
See 1 more Smart Citation